Effect of Tb3+ doping on structural and magnetic properties of CuFe2O4 nanoparticles for biomedical applications - Shrinivas G. Jamdade; Popat S. Tambade; Sopan M. Rathod (Chemistry of Inorganic Materials, 2023)
In the present work, the effect of Tb3+ doping in Cu ferrite is reported. Tb3+ doped Cu ferrite (CuTbxFe2-xO4) (x ​= ​0.0, 0.025, 0.05, 0.075, 0.1, 0.125, and 0.15) nanoparticles have been synthesized by Sol-Gel auto-combustion technique. The CuTbxFe2-xO4 ferrite crystallizes in spinel cubic structure. The presence of secondary phases is noticed. Characterization tools such as XRD, UV–visible, FTIR, and VSM are employed to investigate phase, structure, absorption bands, and magnetic properties. From XRD data the crystallite size is found to be in the range of 2.64–5.07nm. The FTIR pattern of synthesized ferrite describes the asymmetric stretching mode of spinel transition in CuFe2O4. The saturation magnetization of 22.96 emugm−1 is observed for CuFe2O4. From UV–visible DRS spectra the optical band gap energy of Tb3+ doped Cu ferrite samples is determined which shows decrease after doping. The antibacterial and antifungal activity of the synthesized nanoparticles were tested which shows good results.